2015
DOI: 10.1210/jc.2015-2725
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Liraglutide Therapy on Glucagon Secretion in Type 2 Diabetes: Insight From the LIBRA Trial

Abstract: In contrast to its acute glucagon-lowering effect, chronic treatment with liraglutide is associated with increased postchallenge hyperglucagonemia in patients with early T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
1
33
2
Order By: Relevance
“…Indeed, findings in longer-term studies demonstrate that there are long-term differences in hormone levels induced by liraglutide that are not captured in our study. For instance, in a 48-week trial with liraglutide, increases in glucagon levels were observed with liraglutide [77], while we do not observe any changes in glucagon in the 17 days of our trial. Future longitudinal studies are needed to determine short-term versus long-term changes with liraglutide therapy both at low-dose 1.8mg daily and high-dose 3.0mg daily administration.…”
Section: Discussioncontrasting
confidence: 63%
“…Indeed, findings in longer-term studies demonstrate that there are long-term differences in hormone levels induced by liraglutide that are not captured in our study. For instance, in a 48-week trial with liraglutide, increases in glucagon levels were observed with liraglutide [77], while we do not observe any changes in glucagon in the 17 days of our trial. Future longitudinal studies are needed to determine short-term versus long-term changes with liraglutide therapy both at low-dose 1.8mg daily and high-dose 3.0mg daily administration.…”
Section: Discussioncontrasting
confidence: 63%
“…Single-dose experiments have shown that GLP-1 agonists suppress meal-stimulated increases in plasma glucagon levels (23). However, more-recent studies have indicated that treatment with GLP-1 agonists over weeks and months may actually increase circulating plasma glucagon levels; such increases in glucagon may help to explain the limited benefit of liraglutide during CL control in the present study (24). …”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, a recent study by Kramer et al has reported that chronic liraglutide treatment is associated with a paradoxical enhancement in hyperglucagonemia, which emerged 12 weeks after treatment initiation and persists over a 48-week treatment period, together with sustained glycemic control. The authors suggest that the glucose-lowering effects of liraglutide may not be due to the postprandial reduction in glucagon that is observed with short-term treatment, speculating that long-term benefits may be due to α-cell compensation [15]. …”
Section: Discussionmentioning
confidence: 99%